Debating the sacraments print and authority in the early Reformation - Burnett, Amy Nelson 1957- (Oxford University Press, 2019)
"Debating the Sacraments argues that Reformation debates concerning baptism and the Lord's Supper cannot be treated in isolation. It demonstrates the continuing influence of Erasmus on Luther's evangelical opponents and examines the role of printing in fanning the public controversy over the sacraments"...
Includes bibliographical references and index
Keywords: Geschichte 1520-1540; Reformation; Printing -- Europe -- History -- 16th century; Christian literature -- Publishing -- Europe -- History -- 16th century; Book industries and trade -- Europe -- History -- 16th century; Lord's Supper -- History of doctrines; Baptism -- History of doctrines; Evangelische Theologie; Sakrament; Sakramententheologie